2016
DOI: 10.18632/oncotarget.13130
|View full text |Cite
|
Sign up to set email alerts
|

TET2 functions as a resistance factor against DNA methylation acquisition during Epstein-Barr virus infection

Abstract: Extensive DNA methylation is observed in gastric cancer with Epstein-Barr virus (EBV) infection, and EBV infection is the cause to induce this extensivehypermethylaton phenotype in gastric epithelial cells. However, some 5′ regions of genes do not undergo de novo methylation, despite the induction of methylation in surrounding regions, suggesting the existence of a resistance factor against DNA methylation acquisition. We conducted an RNA-seq analysis of gastric epithelial cells with and without EBV infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…However, further studies are needed to elucidate whether the expressional upregulation results in an increased protein level and causes the observed demethylation. In contrast to the HHV-6B effect, TET2 expression is repressed by EBV infection and, as expected, loss of TET2 increases EBV-induced host cell DNA methylation (31). However, TET2-induced hydroxymethylation of EBV promoters can also affect EBV reactivation from latency (32) and can affect the EBV latency type (33).…”
Section: Discussionsupporting
confidence: 58%
“…However, further studies are needed to elucidate whether the expressional upregulation results in an increased protein level and causes the observed demethylation. In contrast to the HHV-6B effect, TET2 expression is repressed by EBV infection and, as expected, loss of TET2 increases EBV-induced host cell DNA methylation (31). However, TET2-induced hydroxymethylation of EBV promoters can also affect EBV reactivation from latency (32) and can affect the EBV latency type (33).…”
Section: Discussionsupporting
confidence: 58%
“…LMP2A induces the STAT3 phosphorylation followed by DNMT1 transcriptionally activation and PTEN promoter methylation, indicating LMP2A plays an essential role in the development and maintenance of EBV-associated cancer [143]. Besides, a resistance factor against DNA methylation namely TET2 was suppressed to contribute to DNA methylation acquisition during EBV infection [144]. Variety of tumor-suppressor genes have been identified to be methylated during EBV infection, such as p16, p14, APC, SSTR1, FHIT, CRBP1, WWOX, DLC-1, AQP3, REC8, TP73, BLU, FSD1, BCL7A, MARK1, SCRN1, and NKX3.1 [129,[145][146][147][148][149][150][151].…”
Section: Genetic and Epigenetic Abnormalities Of Host Cells In Ebvagcmentioning
confidence: 99%
“…We recently showed that TET2 5hmC modifies the EBV genome to promote lytic gene expression in epithelial cells and that NPC tumors lose TET2 expression, which may enhance oncogenesis (47). Furthermore, TET2 was recently found to be a resistance factor of EBV-induced DNA methylation in gastric carcinoma cells, demonstrating that TET2 may have an important role in protection against EBV ϩ tumor development (55). Thus, regulation of TET2 activity may play critical roles in the development of both epithelial and B cell malignancies associated with EBV.…”
Section: Tet2 Promotes Ebv Type III Latency Gene Expressionmentioning
confidence: 99%